2011
DOI: 10.1016/j.is.2010.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Similarity of business process models: Metrics and evaluation

Abstract: a b s t r a c tIt is common for large organizations to maintain repositories of business process models in order to document and to continuously improve their operations. Given such a repository, this paper deals with the problem of retrieving those models in the repository that most closely resemble a given process model or fragment thereof. Up to now, there is a notable research gap on comparing different approaches to this problem and on evaluating them in the same setting. Therefore, this paper presents th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
326
0
33

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 496 publications
(360 citation statements)
references
References 45 publications
1
326
0
33
Order By: Relevance
“…But [24] found that the structural measure performs equally well, i.e. it correctly identifies behaviorally similar and dissimilar processes without looking at behavior.…”
Section: Business Process Model Similaritymentioning
confidence: 96%
See 2 more Smart Citations
“…But [24] found that the structural measure performs equally well, i.e. it correctly identifies behaviorally similar and dissimilar processes without looking at behavior.…”
Section: Business Process Model Similaritymentioning
confidence: 96%
“…Measures for business process model similarity have been investigated thoroughly [21][22][23][24][25][26]. A comprehensive overview can be found in [24].…”
Section: Business Process Model Similaritymentioning
confidence: 99%
See 1 more Smart Citation
“…Similarity of business process models is an active area of research [3,8,9,[12][13][14][15]19]. We distinguish two types of similarity: i) behavioral similarity and ii) structural similarity.…”
Section: Similarity As the 5th Dimensionmentioning
confidence: 99%
“…Notions of inclusion are discussed in work on behavioural equivalence [7,8,9]. Recent works calculate a degree of behavioural similarity between process models based on linguistic, graphmatching, and state-based concepts, see [31] for an overview. Our work instead provides a precise definition of how to determine the behavioural intersection of two process models.…”
Section: Related Workmentioning
confidence: 99%